A combination of biochemical and pathological parameters improves prediction of postresection survival after preoperative chemotherapy in pancreatic cancer: the PANAMA-score - Hank, Thomas; Sandini, Marta; Ferrone, Cristina R.; Ryan, David P.; Mino-Kenudson, Mari; Qadan, Motaz; Wo, Jennifer Y.; Klaiber, Ulla; Weekes, Colin D.; Weniger, Maximilian; Hinz, Ulf; Harrison, Jon M.; et al. (Annals of surgery, 2022)
Objective: - To build a prognostic score for patients with primary chemotherapy undergoing surgery for pancreatic cancer based on pathological parameters and preoperative Carbohydrate antigen 19-9 (CA19-9) levels. - Background: - Prognostic stratification after primary chemotherapy for pancreatic cancer is challenging and prediction models, such as the AJCC staging system, lack validation in the setting of preoperative chemotherapy. - Methods: - Patients with primary chemotherapy resected at the Massachusetts General Hospital between 2007 and 2017 were analyzed. Tumor characteristics independently associated with overall survival were identified and weighted by Cox-proportional regression. The pancreatic neoadjuvant Massachusetts-score (PANAMA-score) was computed from these variables and its performance assessed by Harrel concordance index and area under the receiving characteristics curves analysis. Comparisons were made with the AJCC staging system and external validation was performed in an independent cohort with primary chemotherapy from Heidelberg, Germany. - Results: - A total of 216 patients constituted the training cohort. The multivariate analysis demonstrated tumor size, number of positive lymph-nodes, R-status, and high CA19-9 to be independently associated with overall survival. Kaplan-Meier analysis according to low, intermediate, and high PANAMA-score showed good discriminatory power of the new metrics (P < 0.001). The median overall survival for the three risk-groups was 45, 27, and 12 months, respectively. External validation in 258 patients confirmed the prognostic ability of the score and demonstrated better accuracy compared with the AJCC staging system. - Conclusion: - The proposed PANAMA-score, based on independent predictors of postresection survival, including pathologic variables and CA19-9, not only provides better discrimination compared to the AJCC staging system, but also identifies patients at high-risk for early death.